Pre/post evaluation of a pilot prevention with positives training program for healthcare providers in North West Province, Republic of South Africa - Christopher G. Kemp; Julia de Kadt; Erushka Pillay; Jennifer M. Gilvydis; Evasen Naidoo; Jessica Grignon; Marcia R. Weaver (BMC, 2017)
Abstract Background Prevention interventions for people living with HIV/AIDS are an important component of HIV programs. We report the results of a pilot evaluation of a four-hour, clinic-based training for healthcare providers in South Africa on HIV prevention assessments and messages. This pre/post pilot evaluation examined whether the training was associated with providers delivering more prevention messages. Methods Seventy providers were trained at four public primary care clinics with a high volume of HIV patients. Pre- and post-training patient exit surveys were conducted using Audio-Computer Assisted Structured Interviews. Seven provider appropriate messaging outcomes and one summary provider outcome were compared pre- and post-training using Poisson regression. Results Four hundred fifty-nine patients pre-training and 405 post-training with known HIV status were interviewed, including 175 and 176 HIV positive patients respectively. Among HIV positive patients, delivery of all appropriate messages by providers declined post-training. The summary outcome decreased from 56 to 50%; adjusted rate ratio 0.92 (95% CI = 0.87-0.97). Sensitivity analyses adjusting for training coverage and time since training detected fewer declines. Among HIV negative patients the summary score was stable at 32% pre- and post-training; adjusted rate ratio 1.05 (95% CI = 0.98-1.12). Conclusions Surprisingly, this training was associated with a decrease in prevention messages delivered to HIV positive patients by providers. Limited training coverage and delays between training and post-training survey may partially account for this apparent decrease. A more targeted approach to prevention messages may be more effective.